2021
DOI: 10.3920/bm2020.0233
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Bifidobacterium animalis subsp. lactis, BB-12® on infant colic – a randomised, double-blinded, placebo-controlled study

Abstract: To evaluate the administration of Bifidobacterium animalis subsp. lactis, BB-12® (BB-12) on infant colic in breastfed infants, a double-blind, placebo-controlled randomised study was conducted in Chengdu, China from April 2016 to October 2017 with 192 full-term infants less than 3 months of age and meeting the ROME III criteria for infant colic. After a 1-week run-in the infants were randomly assigned to receive daily BB-12 (1×109 cfu/day) or placebo for 3 weeks. Crying/fussing time were recorded using a 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The subsequent study by Chen et al [ 19 ] examined similar markers and also found an increase in sIgA and butyrate at the end of their 21-day intervention. However, this group found an increase in calprotectin in the fecal samples of the BB-12 group compared to the placebo.…”
Section: Reviewmentioning
confidence: 92%
See 3 more Smart Citations
“…The subsequent study by Chen et al [ 19 ] examined similar markers and also found an increase in sIgA and butyrate at the end of their 21-day intervention. However, this group found an increase in calprotectin in the fecal samples of the BB-12 group compared to the placebo.…”
Section: Reviewmentioning
confidence: 92%
“…Bifidobacterium animalis is a gram-positive anaerobic bacterium that naturally colonizes the gut of humans. Three of the studies that met the inclusion criteria for this review examined this single-strain probiotic in the treatment group [19][20][21]. Two of the three studies [19,20] utilized the same concentration of Bifidobacterium animalis subsp.…”
Section: Bifidobacterium Animalis Subsp Lactismentioning
confidence: 99%
See 2 more Smart Citations
“…A 2021 RCT performed in China (96) in 192 full‐term infants ≤7 weeks, breastfed, with colic according to the Rome III criteria found that compared with placebo, administration of B lactis BB‐12 (1 × 10 9 CFU/day) for 3 weeks significantly increased the treatment success (defined as earlier; RR 2.8, 95% CI: 1.9–4.2). There was also a significant difference between the B lactis BB‐12 and placebo groups in mean daily crying time at the end of intervention (60.8 ± 23.4 vs 95.8 ± 26.0, MD −35 minutes, 95% CI: −42 to −28).…”
Section: Functional Gastrointestinal Disorders (Disorders Of Gut–brai...mentioning
confidence: 99%